Book of the dead - Cornwell, Patricia Daniels (New York : G. P. Putnam's Sons, 2007)
Relocating to Charleston after a particularly grueling case, Dr. Kay Scarpetta opens a private forensic pathology practice but is quickly targeted by local politics and a covert saboteur before a series of violent deaths bring her skills into high view.
Keywords: Scarpetta, Kay (Fictitious character); Medical examiners (Law); Forensic pathologists; Women physicians; South Carolina; Mystery fiction; Medical novels